Strategi Penetapan Tarif Layanan Pendidikan - Anisa Nurul Santi; Dian Khoirun Nissa; Alfan Ghafar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Determining educational service rates is an important strategic step in managing educational institutions. This process involves determining adequate pricing to ensure the desirability and quality of the services provided. This study explores the various strategies used in pricing educational services, including economic, financial, and competitive factors considered. Through in-depth analysis, this research provides insight into how educational institutions can optimize the rate setting process to meet funding needs while maintaining the accessibility and quality of education provided.